2012
DOI: 10.2528/pier12042707
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Multi-Frequency System for Studying Dosimetry and Acute Effects on Cell and Nuclear Morphology in Rat Tissues

Abstract: Abstract-Simultaneous exposure to multiple electromagnetic signals with widely differing carrier frequencies is a reality of daily life, but its possible effects on health are unknown. In this study, we exposed rats to non-thermal levels of 900 and 2450 MHz TEM-mode radiation, applied individually or simultaneously, and we obtained estimates of 1 g mean SAR (specific absorption rate) in various tissues using a numerical model of the rat and finite-difference timedomain software. The experimental system compris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The apparent absence of biological effects on rat tissue morphology was inconclusive in a prior study [ 13 ] that compared biological effects of a single RF with those of two simultaneous RF signals. In contrast, the current work allowed us to experimentally determine that the biological effects of the simultaneous interaction of radiofrequencies were neither additive nor greater than the effects of applying each signal separately.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The apparent absence of biological effects on rat tissue morphology was inconclusive in a prior study [ 13 ] that compared biological effects of a single RF with those of two simultaneous RF signals. In contrast, the current work allowed us to experimentally determine that the biological effects of the simultaneous interaction of radiofrequencies were neither additive nor greater than the effects of applying each signal separately.…”
Section: Discussionmentioning
confidence: 99%
“…In previous work, we observed that the acute interaction of several radiofrequencies with non-thermal SAR did not increase cellular apoptosis in eight different types of tissue [ 13 ]. However, in the current work we found a significant increase in pre-apoptotic activity (see Results).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies (not included in Table 8 ), restrained male rats were exposed at up to 0.2 W/kg in a GTEM cell, and SARs were estimated using numerical phantoms. In the first study, it was reported that single or simultaneous exposure had no effect on cellular morphology and apoptosis in eight tissues, including the brain, muscle, and testicles ( 54 ). In the second study, effects on cellular stress responses were investigated in the cerebral cortex and cerebellum ( 55 ).…”
Section: Summary Of Studies With Animalsmentioning
confidence: 99%
“…This leads to users being exposed to the RF electromagnetic radiation emitted by mobile communication equipment, such as cellular phones. Concern about possible health effects due to exposures to electromagnetic fields (EMs) has increased among the public and professionals since these communication devices have proliferated around the globe [1][2][3][4][5][6][7][8]. This concern has caused an increase in the research emphasis on analyzing the rate at which electromagnetic radiation is being absorbed by the human body [1][2][3][4][5][6][7][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%